The Importance of Human Emotions for Wildlife Conservation - Castillo-Huitrón, Nathalia M.; Naranjo, Eduardo J.; Santos-Fita, Dídac; Estrada-Lugo, Erin (Frontiers in Psychology, 2020)
Animals have always been important for human life due to the ecological, cultural and economic functions that they represent. This has allowed building several kinds of relationships that have promoted different emotions in human societies. The objective of this review was to identify the main emotions that humans show towards wildlife species and the impact of such emotions on animal populations’ management. We reviewed academic databases to identify previous studies on this topic worldwide. An analysis of the emotions on wildlife and factors causing them is described here. We identified a controversy about these emotions. Large predators such as wolves, coyotes, bears, big felids, as well as reptiles such as snakes and geckos promote mainly anger, fear, and disgust. This is likely due to the perceptions, beliefs and experiences that societies have historically built around them. However, in some social groups these animals have promoted emotions such as happiness due to their values for people. Likewise, sadness is an emotion expressed for the threatening situations that animals are facing nowadays. Furthermore, we associated the conservation status of wildlife species identified in the study with human emotions to discuss their relevance for emerging conservation strategies, particularly focused on endangered species promoting ambiguous emotions in different social groups.